Inventory Management Model Based on Lean Supply Chain to Increase the Service Level in a Distributor of Automotive Sector - Edgar D. Ramos; Timothy J. Pettit; Monika Flanigan; Luis Romero; Katherine Huayta (International Journal of Supply Chain Management, 2020)
This paper deals with the management of spare parts in the automotive sector using Lean practices in a synergistic manner. Managing cost-effective spare parts is essential for manufacturing and service companies. One of the most difficult challenges in effective management of spare parts is to manage and control the levels of stock. Effective management is essential to achieve the best service level in the automotive industry, unfortunately it is an industry which faces a great uncertainty in the demand for spare parts. The management of spare parts is difficult due to the infrequent profile that characterizes market demand. This creates a challenge among the distributors who need to have a large number of items (part numbers) in stock to avoid loss of sales. This paper shows the results of a case study on demand forecast of spare parts and inventory control, selecting the best policies within each SKU category. The methodologies achieved a reduction of the stock rupture, savings in purchases of supplies and greater fulfillment of orders that generated an increase of 22.49% in Sales.